Kualitas fisik dan kimia dedak padi yang difermentasi dengan isolat mikroba rumen (Actinobacilus sp. ML-08) pada level yang berbeda - Nurul Azizah; Ristaqul Husna Belgania; Mirni Lamid; Kadek Rachmawati (Livestock and Animal Research, 2022)
Objective: This study aims to prove the potential of Actinobacillus sp. ML-08 as a fermentation starter to increase the physical and chemical qualities of rice bran.Methods: The experimental was arranged on completely randomized design. The sample was using 5 kg of rice bran with the addition of 4 grams of molasses and Actinobacillus sp. ML-08 with six different levels (0, 5, 10, 15, and 20%) and four replications, then 7 days of facultative anaerobes fermentation. The physical examination used visual observation and the chemical examination used proximate analysis. The data obtained was conducted by analysis of variance followed by Duncan's Multiple Range Test (DMRT).Results: The physical quality of fermented rice bran obtained a change in color from light brown to dark brown, as well as a change in fragrance. Value of pH and Indications of fungi did not show significant (p>0.05). The average pH in all treatments tends to be acidic with a range of 4.63–5.25. The results of the chemical examination showed that the addition of 4gram molasses and Actinobacilus sp. ML-08 at different doses (T2-T5) reduced crude fiber and increased protein, organic matter, and nitrogen free extract compared to T0 and T1 (p<0.05). Actinobacillus sp. ML-08 dose of 5% (T2) was seen as the most effective and optimal in reducing crude fiber 17.58%, and increasing crude protein 13.30%, organic matter 90.12%, and extract material without nitrogen 42.57%.Conclusions: Rice bran fermentation with the addition of Actinobacillus sp. ML-08 5% has potential to decrease crude fiber and increase physical quality, crude protein, organic matter, and nitrogen free extract.